Demokrasi dan Pemilu Kepala Daerah - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Imas Sumiati (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Telescoped Indonesian democracy with the election of regional heads lenses are not adequate. Democracy will be up and flying, when the pillars; power system, system of government, political system, and other powerful systems and stake. If the stake was false pillar, pretending to be just as if, then even this democracy only 'Mastur stale'; as though and pretended firm, ostensibly strong, but weak and limp.The most important issue in the election of regional heads or even any election is how far the effectiveness of the election itself. So far the election is generally less effective. Voters and the candidates chosen to satisfy lust is merely political, to be a winner. All realized, including the election, when in the course of five years. Let alone the concept to advance the region, even gave the concept to themselves as the regional head did not recognize. Eventually bring the area and positioned himself on a targeted orientation (disorientation)